Preparation method of high-strength disposable bioreactor bag

By adding modified materials to the outer and middle layers of the bioreaction bag, a high-strength disposable bioreaction bag was prepared, which solved the problem of low mechanical strength of the existing bioreaction bags and achieved better mechanical properties and barrier properties. .

CN118652459BActive Publication Date: 2025-02-25ZIBO HUA ZHI LIN PACKING PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411142861.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-02-25
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

The existing three-dimensional three-dimensional biological reaction bag has low mechanical strength, which is prone to bag rupture and culture liquid leakage.

Method used

A mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers was added to the outer layer, and a mixture of modified nanomolybdenum disulfide, nanosilicon dioxide and nanotitanium dioxide was added to the intermediate layer, and the mixture of modified nanomolybdenum disulfide, nanosilicon dioxide and nanotitanium dioxide was added to the intermediate layer, and the mixture was coextruded. and heat treatment to prepare high-strength disposable bioreaction bags.

Benefits of technology

The mechanical properties and gas barrier properties of the bioreaction bag are improved, and the bag body rupture and culture liquid leakage are avoided, and the performance is stable.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of disposable bioreactor bag preparation, and specifically relates to a method for preparing a high-strength disposable bioreactor bag. The preparation method comprises the following steps: (1) preparing a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers; (2) preparing a mixture of modified nano molybdenum disulfide, nano silicon dioxide and nano titanium dioxide; (3) mixing outer layer raw materials; (4) mixing middle layer raw materials; (5) respectively melt-extruding the outer layer raw materials, the middle layer raw materials and the inner layer raw materials, co-extruding and forming, and preparing a composite film composed of an outer layer, a middle layer and an inner layer through heat treatment, and finally processing the composite film into a high-strength disposable bioreactor bag. The preparation method of the high-strength disposable bioreactor bag of the present invention has a simple process, and the performance of the prepared bioreactor bag is stable, so that the bag body of the bioreactor bag can be prevented from rupturing and leakage of the culture medium in the bag during use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of disposable bioreactor bag preparation, and specifically relates to a method for preparing a high-strength disposable bioreactor bag. Background Art

[0002] A disposable bioreactor or disposable bioreactor is a bioreactor that uses a disposable bag instead of a culture container made of stainless steel or glass. In the current biopharmaceutical process, in order to achieve commercial mass production of biological products such as enzymes, antibodies or antibiotics, animal, plant or microbial cells are usually placed in a bioreactor for sterile culture. During this period, the biological fluid is controlled by controlling the mixing system, gas supply and sensor probe monitoring to obtain the desired biological product. In recent years, as the quality requirements of biological products take into account aspects such as ease of operation and cost control, disposable bioreactors have been widely used in the biological cell culture market.

[0003] In order to meet the needs of commercial mass production, bioreactor bags are generally designed as large-capacity three-dimensional bags. Due to the low mechanical strength of existing three-dimensional bags, the bag body is prone to rupture and leakage of culture liquid in the bag during use. Therefore, it is necessary to explore a new method for preparing disposable bioreactor bags. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a high-strength disposable bioreactor bag. The disposable bioreactor bag prepared by the method has good mechanical properties and barrier properties.

[0005] The method for preparing the high-strength disposable bioreactor bag of the present invention comprises the following steps:

[0006] (1) Preparation of a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers

[0007] ① 3-glycidyloxypropyltriethoxysilane, deionized water and anhydrous ethanol were mixed in a mass ratio of 1:1:15, and pre-hydrolyzed at room temperature and pressure for 50-60 minutes to prepare a pre-hydrolyzed silane coupling agent;

[0008] ② stirring and mixing the mixture of magnesium borate whiskers, zirconium diboride and cellulose nanofibers with the pre-hydrolyzed silane coupling agent prepared above evenly;

[0009] ③ After centrifugal separation, drying at 85-90° C. for 5-5.5 hours, a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers is prepared;

[0010] (2) Preparation of a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide

[0011] ① Adding a mixture of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide to a first anhydrous ethanol solution and ultrasonically treating the mixture for 1.5-1.7 hours to prepare a first mixed system;

[0012] ② Add KH570 silane coupling agent to the second anhydrous ethanol solution, then add oxalic acid to adjust the pH value of the system to 4.5, stir and react for 2.2-2.4 hours to prepare a second mixed system;

[0013] ③ The first mixed system and the second mixed system are mixed, magnetically stirred at 63-65° C. for 3.5-4 hours, and then centrifuged, and the resulting precipitate is dried at 75-77° C. for 4.3-4.5 hours to prepare a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide;

[0014] (3) Mixing of outer layer raw materials

[0015] uniformly mixing a mixture of metallocene linear low-density polyethylene, low-density polyethylene, ethylene-ethyl acrylate copolymer, and the modified magnesium borate whiskers, zirconium diboride, and cellulose nanofibers prepared in step (1);

[0016] (4) Mixing of raw materials for the middle layer

[0017] Evenly mix the metallocene linear low-density polyethylene, linear low-density polyethylene, low-density polyethylene, maleic anhydride grafted polyethylene, and the mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide prepared in step (2);

[0018] (5) The outer layer raw material uniformly mixed in step (3), the middle layer raw material uniformly mixed in step (4), and the inner layer raw material uniformly mixed in step (4) are melt-extruded through an extruder respectively, and then enter a co-extrusion die through various flow channels for co-extrusion molding, and a composite film consisting of an outer layer, a middle layer, and an inner layer is prepared through heat treatment, and finally the composite film is processed into a high-strength disposable bioreactor bag.

[0019] in:

[0020] In step (1) ②, the mass ratio of magnesium borate whiskers, zirconium diboride and cellulose nanofibers to the pre-hydrolyzed silane coupling agent is 1:0.03.

[0021] In step (1)②, the mass ratio of magnesium borate whiskers, zirconium diboride and cellulose nanofibers is 1: 0.7-0.9: 1.2-1.3.

[0022] The first anhydrous ethanol solution and the second anhydrous ethanol solution in step (2) have the same composition, both being a mixture of anhydrous ethanol and deionized water in a volume ratio of 9:1.

[0023] In step (2)①, the mass and volume ratio of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide to the first anhydrous ethanol solution is 1:20, in units of g / mL.

[0024] In step (2)①, the mass ratio of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide is 1.2-1.4: 0.7-0.8: 0.55-0.65.

[0025] In step (2) ②, the KH570 silane coupling agent accounts for 6-8% of the volume of the second anhydrous ethanol solution.

[0026] The volume of the first anhydrous ethanol solution in step (2) ① is equal to the volume of the second anhydrous ethanol solution in step (2) ②.

[0027] In step (3), the outer layer raw material composition is as follows, calculated by weight: 85-87 parts of metallocene linear low-density polyethylene, 13-15 parts of low-density polyethylene, 2-3 parts of ethylene-ethyl acrylate copolymer, and 8-10 parts of a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers.

[0028] In step (4), the raw material composition of the intermediate layer is as follows, in parts by weight: 44-46 parts of metallocene linear low-density polyethylene, 31-33 parts of linear low-density polyethylene, 21-25 parts of low-density polyethylene, 3-5 parts of maleic anhydride grafted polyethylene, and 6.7-7.5 parts of a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide.

[0029] The metallocene linear low-density polyethylene used in the raw materials for the outer layer and the middle layer is 1018MA produced by ExxonMobil Corporation of the United States, and the low-density polyethylene is 2420D produced by Daqing Petrochemical.

[0030] The linear low-density polyethylene in the middle layer raw material is DFDA-7042 produced by Sinopec Shanghai Petrochemical Co., Ltd.

[0031] In step (5), the inner layer raw material is 100 parts of random copolymer polypropylene, and the density of random copolymer polypropylene is 0.910 g / cm 3 The melt index is 8.0g / 10min. The manufacturer is Sinopec Shanghai Petrochemical Co., Ltd. and the brand is F800EDF.

[0032] In step (5), the melt extrusion temperature of the inner layer raw material is 190-195°C; the melt extrusion temperature of the outer layer raw material is 190-200°C; the melt extrusion temperature of the middle layer raw material is 175-195°C; and the co-extrusion temperature is 210-215°C.

[0033] In step (5), the heat treatment temperature is 120-125° C. and the heat treatment time is 17-17.5 h.

[0034] The preparation method of the high-strength disposable bioreactor bag of the present invention adds a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers in the outer layer to ensure the mechanical strength of the bioreactor bag. First, magnesium borate whiskers, zirconium diboride and cellulose nanofibers are modified to improve their dispersibility in polyethylene. Wherein, the cellulose nanofibers contain groups such as carboxyl and hydroxyl groups on their surfaces while having nanoparticle characteristics, and through modification, the mechanical properties of the composite material can be significantly improved. Magnesium borate whiskers have the characteristics of large aspect ratio, corrosion resistance, high strength and high elastic modulus, and the atomic planes of boron and zirconium in the zirconium diboride crystal structure alternately appear to form a two-dimensional network structure, and the strong bond of the Zr-B ionic bond between the BB covalent bond and the boron atom and the zirconium atomic plane makes it have high strength, high hardness and stability. Therefore, the mechanical properties of the reaction bag are further enhanced by additionally adding magnesium borate whiskers and zirconium diboride. When the reaction bag is subjected to stress, cellulose nanofibers, magnesium borate whiskers and zirconium diboride become the main load-bearing components, which effectively bear stress to avoid stress concentration and ensure that the reaction bag has good mechanical properties. In addition, ethylene-ethyl acrylate copolymer is added to the outer layer raw material. The addition of ethylene-ethyl acrylate copolymer can increase the amount of the mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers, while improving the elasticity, environmental stress cracking resistance and impact resistance of the prepared reaction bag.

[0035] The preparation method of the high-strength disposable bioreactor bag of the present invention adds a mixture of modified nano molybdenum disulfide, nano silicon dioxide and nano titanium dioxide in the middle layer to improve the gas barrier property of the reaction bag. The mixture of nano molybdenum disulfide, nano silicon dioxide and nano titanium dioxide is modified by using KH570 silane coupling agent to improve the compatibility with polyethylene. Molybdenum disulfide nanosheets have a large specific surface area and a high aspect ratio. The high aspect ratio and high orientation of molybdenum disulfide are used to improve the gas barrier property of the disposable bioreactor bag, and molybdenum disulfide is used as the main component. Nano rod-shaped titanium dioxide and nano silicon dioxide can induce nucleation crystallization in polyethylene film, reduce the free volume of polyethylene film, and the perfect crystal structure in the polymer can prevent the smallest gas molecules from penetrating and diffusing in the polymer, thereby improving the barrier property of the composite film. In addition, since nano-silica is a rigid particle, it can promote shear yield of the matrix during the fracture process by integrating well with the polyethylene matrix, absorbing a large amount of plastic deformation energy to increase the elastic modulus of the polyethylene film, thereby improving its mechanical properties.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The method for preparing a high-strength disposable bioreactor bag of the present invention ensures the mechanical properties of the prepared bioreactor bag by adding a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers in the outer layer, and ensures the barrier properties of the prepared bioreactor bag by adding a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide in the middle layer, which is compounded with the inner polypropylene layer, so that the prepared disposable bioreactor bag has excellent mechanical properties and barrier properties.

[0038] (2) The method for preparing the high-strength disposable bioreactor bag of the present invention has a simple process and the prepared bioreactor bag has stable performance, thereby preventing the bioreactor bag from rupturing and leaking the culture fluid in the bag during use. DETAILED DESCRIPTION

[0039] The present invention is further described below with reference to the embodiments.

[0040] Example 1

[0041] The method for preparing the high-strength disposable bioreactor bag described in Example 1 comprises the following steps:

[0042] (1) Preparation of a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers

[0043] ① 3-glycidyloxypropyltriethoxysilane, deionized water and anhydrous ethanol were mixed in a mass ratio of 1:1:15, and pre-hydrolyzed at room temperature and pressure for 55 minutes to prepare a pre-hydrolyzed silane coupling agent;

[0044] ② stirring and mixing the mixture of magnesium borate whiskers, zirconium diboride and cellulose nanofibers with the pre-hydrolyzed silane coupling agent prepared above evenly;

[0045] ③ After centrifugal separation, the mixture was dried at 88°C for 5.3 hours to prepare a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers;

[0046] (2) Preparation of a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide

[0047] ① Adding a mixture of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide to a first anhydrous ethanol solution and ultrasonically treating the mixture for 1.6 hours to prepare a first mixed system;

[0048] ② Add KH570 silane coupling agent to the second anhydrous ethanol solution, then add oxalic acid to adjust the pH value of the system to 4.5, stir and react for 2.3 hours to prepare a second mixed system;

[0049] ③ The first mixed system and the second mixed system were mixed, magnetically stirred at 64° C. for 3.7 hours, and then centrifuged, and the resulting precipitate was dried at 76° C. for 4.4 hours to prepare a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide;

[0050] (3) Mixing of outer layer raw materials

[0051] uniformly mixing a mixture of metallocene linear low-density polyethylene, low-density polyethylene, ethylene-ethyl acrylate copolymer, and the modified magnesium borate whiskers, zirconium diboride, and cellulose nanofibers prepared in step (1);

[0052] (4) Mixing of raw materials for the middle layer

[0053] Evenly mix the metallocene linear low-density polyethylene, linear low-density polyethylene, low-density polyethylene, maleic anhydride grafted polyethylene, and the mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide prepared in step (2);

[0054] (5) The outer layer raw material uniformly mixed in step (3), the middle layer raw material uniformly mixed in step (4), and the inner layer raw material uniformly mixed in step (4) are melt-extruded through an extruder respectively, and then enter a co-extrusion die through various flow channels for co-extrusion molding, and a composite film consisting of an outer layer, a middle layer, and an inner layer is prepared through heat treatment, and finally the composite film is processed into a high-strength disposable bioreactor bag.

[0055] in:

[0056] In step (1) ②, the mass ratio of magnesium borate whiskers, zirconium diboride and cellulose nanofibers to the pre-hydrolyzed silane coupling agent is 1:0.03.

[0057] In step (1)②, the mass ratio of magnesium borate whiskers, zirconium diboride and cellulose nanofibers is 1: 0.8: 1.25.

[0058] The first anhydrous ethanol solution and the second anhydrous ethanol solution in step (2) have the same composition, both being a mixture of anhydrous ethanol and deionized water in a volume ratio of 9:1.

[0059] In step (2)①, the mass and volume ratio of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide to the first anhydrous ethanol solution is 1:20, in units of g / mL.

[0060] In step (2)①, the mass ratio of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide is 1.3:0.75:0.60.

[0061] In step (2) ②, the KH570 silane coupling agent accounts for 7% of the volume of the second anhydrous ethanol solution.

[0062] The volume of the first anhydrous ethanol solution in step (2) ① is equal to the volume of the second anhydrous ethanol solution in step (2) ②.

[0063] In step (3), the outer layer raw material composition is as follows, calculated by weight: 86 parts of metallocene linear low-density polyethylene, 14 parts of low-density polyethylene, 2.5 parts of ethylene-ethyl acrylate copolymer, and 9 parts of a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers.

[0064] In step (4), the raw material composition of the intermediate layer is as follows, calculated by weight: 45 parts of metallocene linear low-density polyethylene, 32 parts of linear low-density polyethylene, 23 parts of low-density polyethylene, 4 parts of maleic anhydride grafted polyethylene, and 7.1 parts of a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide.

[0065] The metallocene linear low-density polyethylene used in the raw materials for the outer layer and the middle layer is 1018MA produced by ExxonMobil Corporation of the United States, and the low-density polyethylene is 2420D produced by Daqing Petrochemical.

[0066] The linear low-density polyethylene in the middle layer raw material is DFDA-7042 produced by Sinopec Shanghai Petrochemical Co., Ltd.

[0067] In step (5), the inner layer raw material is 100 parts of random copolymer polypropylene, and the density of random copolymer polypropylene is 0.910 g / cm 3 The melt index is 8.0g / 10min. The manufacturer is Sinopec Shanghai Petrochemical Co., Ltd. and the brand is F800EDF.

[0068] In step (5), the melt extrusion temperature of the inner layer raw material is 193°C; the melt extrusion temperature of the outer layer raw material is 195°C; the melt extrusion temperature of the middle layer raw material is 185°C; and the co-extrusion temperature is 213°C.

[0069] In step (5), the heat treatment temperature is 123° C. and the heat treatment time is 17.3 h.

[0070] The water vapor permeability of the high-strength disposable bioreactor bag prepared in Example 1 is 0.3 g / m 2 *24h*0.1MPa, oxygen permeability is 0.5cm 3 / m 2 *24h*0.1MPa, tensile strength is 82.2MPa.

[0071] Example 2

[0072] The method for preparing the high-strength disposable bioreactor bag described in Example 2 comprises the following steps:

[0073] (1) Preparation of a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers

[0074] ① 3-glycidyloxypropyltriethoxysilane, deionized water and anhydrous ethanol were mixed in a mass ratio of 1:1:15, and pre-hydrolyzed at room temperature and pressure for 50 minutes to prepare a pre-hydrolyzed silane coupling agent;

[0075] ② stirring and mixing the mixture of magnesium borate whiskers, zirconium diboride and cellulose nanofibers with the pre-hydrolyzed silane coupling agent prepared above evenly;

[0076] ③ After centrifugal separation, the mixture was dried at 85°C for 5 hours to prepare a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers;

[0077] (2) Preparation of a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide

[0078] ① Adding a mixture of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide to a first anhydrous ethanol solution and ultrasonically treating the mixture for 1.7 hours to prepare a first mixed system;

[0079] ② Add KH570 silane coupling agent to the second anhydrous ethanol solution, then add oxalic acid to adjust the pH value of the system to 4.5, stir and react for 2.4 hours to prepare a second mixed system;

[0080] ③ The first mixed system and the second mixed system were mixed, magnetically stirred at 65° C. for 4 h, and then centrifuged, and the resulting precipitate was dried at 77° C. for 4.5 h to prepare a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide;

[0081] (3) Mixing of outer layer raw materials

[0082] uniformly mixing a mixture of metallocene linear low-density polyethylene, low-density polyethylene, ethylene-ethyl acrylate copolymer, and the modified magnesium borate whiskers, zirconium diboride, and cellulose nanofibers prepared in step (1);

[0083] (4) Mixing of raw materials for the middle layer

[0084] Evenly mix the metallocene linear low-density polyethylene, linear low-density polyethylene, low-density polyethylene, maleic anhydride grafted polyethylene, and the mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide prepared in step (2);

[0085] (5) The outer layer raw material uniformly mixed in step (3), the middle layer raw material uniformly mixed in step (4), and the inner layer raw material uniformly mixed in step (4) are melt-extruded through an extruder respectively, and then enter a co-extrusion die through various flow channels for co-extrusion molding, and a composite film consisting of an outer layer, a middle layer, and an inner layer is prepared through heat treatment, and finally the composite film is processed into a high-strength disposable bioreactor bag.

[0086] in:

[0087] In step (1) ②, the mass ratio of magnesium borate whiskers, zirconium diboride and cellulose nanofibers to the pre-hydrolyzed silane coupling agent is 1:0.03.

[0088] In step (1)②, the mass ratio of magnesium borate whiskers, zirconium diboride and cellulose nanofibers is 1: 0.7: 1.3.

[0089] The first anhydrous ethanol solution and the second anhydrous ethanol solution in step (2) have the same composition, both being a mixture of anhydrous ethanol and deionized water in a volume ratio of 9:1.

[0090] In step (2)①, the mass and volume ratio of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide to the first anhydrous ethanol solution is 1:20, in units of g / mL.

[0091] In step (2)①, the mass ratio of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide is 1.4:0.7:0.55.

[0092] In step (2) ②, the KH570 silane coupling agent accounts for 8% of the volume of the second anhydrous ethanol solution.

[0093] The volume of the first anhydrous ethanol solution in step (2) ① is equal to the volume of the second anhydrous ethanol solution in step (2) ②.

[0094] In step (3), the outer layer raw material composition is as follows, calculated by weight: 87 parts of metallocene linear low-density polyethylene, 13 parts of low-density polyethylene, 2 parts of ethylene-ethyl acrylate copolymer, and 8 parts of a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers.

[0095] In step (4), the raw material composition of the intermediate layer is as follows, measured in parts by weight: 44 parts of metallocene linear low-density polyethylene, 31 parts of linear low-density polyethylene, 25 parts of low-density polyethylene, 5 parts of maleic anhydride grafted polyethylene, and 7.5 parts of a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide.

[0096] The metallocene linear low-density polyethylene used in the raw materials for the outer layer and the middle layer is 1018MA produced by ExxonMobil Corporation of the United States, and the low-density polyethylene is 2420D produced by Daqing Petrochemical.

[0097] The linear low-density polyethylene in the middle layer raw material is DFDA-7042 produced by Sinopec Shanghai Petrochemical Co., Ltd.

[0098] In step (5), the inner layer raw material is 100 parts of random copolymer polypropylene, and the density of random copolymer polypropylene is 0.910 g / cm 3 The melt index is 8.0g / 10min. The manufacturer is Sinopec Shanghai Petrochemical Co., Ltd. and the brand is F800EDF.

[0099] In step (5), the melt extrusion temperature of the inner layer raw material is 190°C; the melt extrusion temperature of the outer layer raw material is 190°C; the melt extrusion temperature of the middle layer raw material is 195°C; and the co-extrusion temperature is 215°C.

[0100] In step (5), the heat treatment temperature is 125° C. and the heat treatment time is 17 h.

[0101] The water vapor permeability of the high-strength disposable bioreactor bag prepared in Example 2 is 0.3 g / m 2 *24h*0.1MPa, oxygen permeability is 0.4m 3 / m 2 *24h*0.1MPa, tensile strength is 81.5MPa.

[0102] Example 3

[0103] The method for preparing the high-strength disposable bioreactor bag described in Example 3 comprises the following steps:

[0104] (1) Preparation of a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers

[0105] ① 3-glycidyloxypropyltriethoxysilane, deionized water and anhydrous ethanol were mixed in a mass ratio of 1:1:15, and pre-hydrolyzed at room temperature and pressure for 60 minutes to prepare a pre-hydrolyzed silane coupling agent;

[0106] ② stirring and mixing the mixture of magnesium borate whiskers, zirconium diboride and cellulose nanofibers with the pre-hydrolyzed silane coupling agent prepared above evenly;

[0107] ③ After centrifugal separation, the mixture was dried at 90°C for 5.5 hours to prepare a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers;

[0108] (2) Preparation of a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide

[0109] ① Adding a mixture of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide to a first anhydrous ethanol solution and ultrasonically treating the mixture for 1.5 hours to prepare a first mixed system;

[0110] ② Add KH570 silane coupling agent to the second anhydrous ethanol solution, then add oxalic acid to adjust the pH value of the system to 4.5, stir and react for 2.2 hours to prepare a second mixed system;

[0111] ③ The first mixed system and the second mixed system were mixed, magnetically stirred at 63° C. for 3.5 h, and then centrifuged, and the resulting precipitate was dried at 75° C. for 4.3 h to prepare a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide;

[0112] (3) Mixing of outer layer raw materials

[0113] uniformly mixing a mixture of metallocene linear low-density polyethylene, low-density polyethylene, ethylene-ethyl acrylate copolymer, and the modified magnesium borate whiskers, zirconium diboride, and cellulose nanofibers prepared in step (1);

[0114] (4) Mixing of raw materials for the middle layer

[0115] Evenly mix the metallocene linear low-density polyethylene, linear low-density polyethylene, low-density polyethylene, maleic anhydride grafted polyethylene, and the mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide prepared in step (2);

[0116] (5) The outer layer raw material uniformly mixed in step (3), the middle layer raw material uniformly mixed in step (4), and the inner layer raw material uniformly mixed in step (4) are melt-extruded through an extruder respectively, and then enter a co-extrusion die through various flow channels for co-extrusion molding, and a composite film consisting of an outer layer, a middle layer, and an inner layer is prepared through heat treatment, and finally the composite film is processed into a high-strength disposable bioreactor bag.

[0117] in:

[0118] In step (1) ②, the mass ratio of magnesium borate whiskers, zirconium diboride and cellulose nanofibers to the pre-hydrolyzed silane coupling agent is 1:0.03.

[0119] In step (1)②, the mass ratio of magnesium borate whiskers, zirconium diboride and cellulose nanofibers is 1: 0.9: 1.2.

[0120] The first anhydrous ethanol solution and the second anhydrous ethanol solution in step (2) have the same composition, both being a mixture of anhydrous ethanol and deionized water in a volume ratio of 9:1.

[0121] In step (2)①, the mass and volume ratio of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide to the first anhydrous ethanol solution is 1:20, in units of g / mL.

[0122] In step (2)①, the mass ratio of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide is 1.2:0.8:0.65.

[0123] In step (2) ②, the KH570 silane coupling agent accounts for 6% of the volume of the second anhydrous ethanol solution.

[0124] The volume of the first anhydrous ethanol solution in step (2) ① is equal to the volume of the second anhydrous ethanol solution in step (2) ②.

[0125] In step (3), the outer layer raw material composition is as follows, calculated by weight: 85 parts of metallocene linear low-density polyethylene, 15 parts of low-density polyethylene, 3 parts of ethylene-ethyl acrylate copolymer, and 10 parts of a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers.

[0126] In step (4), the composition of the intermediate layer raw materials is as follows, in parts by weight: 46 parts of metallocene linear low-density polyethylene, 33 parts of linear low-density polyethylene, 21 parts of low-density polyethylene, 3 parts of maleic anhydride grafted polyethylene, and 6.7 parts of a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide.

[0127] The metallocene linear low-density polyethylene used in the raw materials for the outer layer and the middle layer is 1018MA produced by ExxonMobil Corporation of the United States, and the low-density polyethylene is 2420D produced by Daqing Petrochemical.

[0128] The linear low-density polyethylene in the middle layer raw material is DFDA-7042 produced by Sinopec Shanghai Petrochemical Co., Ltd.

[0129] In step (5), the inner layer raw material is 100 parts of random copolymer polypropylene, and the density of random copolymer polypropylene is 0.910 g / cm 3 The melt index is 8.0g / 10min. The manufacturer is Sinopec Shanghai Petrochemical Co., Ltd. and the brand is F800EDF.

[0130] In step (5), the melt extrusion temperature of the inner layer raw material is 195°C; the melt extrusion temperature of the outer layer raw material is 200°C; the melt extrusion temperature of the middle layer raw material is 175°C; and the co-extrusion temperature is 210°C.

[0131] In step (5), the heat treatment temperature is 120° C. and the heat treatment time is 17.5 h.

[0132] The water vapor permeability of the high-strength disposable bioreactor bag prepared in Example 3 is 0.5 g / m2 *24h*0.1MPa, oxygen permeability is 0.6cm 3 / m 2 *24h*0.1MPa, tensile strength is 80.8MPa.

[0133] Comparative Example 1

[0134] The method for preparing the disposable bioreactor bag described in this comparative example 1 is different from that in Example 1 in that step (1) is omitted, and the mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers is no longer added to the outer layer raw material described in step (3), and the remaining steps are the same as those in Example 1.

[0135] The water vapor permeability of the disposable bioreactor bag prepared in Comparative Example 1 was 1.4 g / m 2 *24h*0.1MPa, oxygen permeability is 2.2cm 3 / m 2 *24h*0.1MPa, tensile strength is 61.4MPa.

[0136] Comparative Example 2

[0137] The method for preparing the disposable bioreactor bag described in this comparative example 2 is different from that in Example 1 in that step (2) is omitted, and the mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide is no longer added to the intermediate layer raw material described in step (4). The remaining steps are the same as those in Example 1.

[0138] The water vapor permeability of the disposable bioreactor bag prepared in Comparative Example 2 was 2.1 g / m 2 *24h*0.1MPa, oxygen permeability is 3.0cm 3 / m 2 *24h*0.1MPa, tensile strength is 69.5MPa.

Claims

1. A method for preparing a high-strength disposable bioreactor bag, characterized in that: It consists of the following steps: (1) Preparation of a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers ① 3-glycidyloxypropyltriethoxysilane, deionized water and anhydrous ethanol were mixed in a mass ratio of 1:1:15, and pre-hydrolyzed at room temperature and pressure for 50-60 minutes to prepare a pre-hydrolyzed silane coupling agent; ② stirring and mixing the mixture of magnesium borate whiskers, zirconium diboride and cellulose nanofibers with the pre-hydrolyzed silane coupling agent prepared above evenly; ③ After centrifugal separation, drying at 85-90° C. for 5-5.5 hours, a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers is prepared; (2) Preparation of a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide ① Adding a mixture of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide to a first anhydrous ethanol solution and ultrasonically treating the mixture for 1.5-1.7 hours to prepare a first mixed system; ② Add KH570 silane coupling agent to the second anhydrous ethanol solution, then add oxalic acid to adjust the pH value of the system to 4.5, stir and react for 2.2-2.4 hours to prepare a second mixed system; ③ The first mixed system and the second mixed system are mixed, magnetically stirred at 63-65° C. for 3.5-4 hours, and then centrifuged, and the resulting precipitate is dried at 75-77° C. for 4.3-4.5 hours to prepare a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide; (3) Mixing of outer layer raw materials uniformly mixing a mixture of metallocene linear low-density polyethylene, low-density polyethylene, ethylene-ethyl acrylate copolymer, and the modified magnesium borate whiskers, zirconium diboride, and cellulose nanofibers prepared in step (1); (4) Mixing of raw materials for the middle layer Evenly mix the metallocene linear low-density polyethylene, linear low-density polyethylene, low-density polyethylene, maleic anhydride grafted polyethylene, and the mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide prepared in step (2); (5) the outer layer raw material uniformly mixed in step (3), the middle layer raw material uniformly mixed in step (4) and the inner layer raw material are melted and extruded respectively through an extruder, and then enter the co-extrusion die through each flow channel for co-extrusion molding, and heat-treated to obtain a composite film consisting of an outer layer, a middle layer and an inner layer, and finally the composite film is processed into a high-strength disposable bioreactor bag; Wherein: the inner layer raw material in step (5) is 100 parts of random copolymer polypropylene, and the density of random copolymer polypropylene is 0.910 g / cm 3 , the melt index is 8.0g / 10min.

2. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: In step (1)②, the mass ratio of magnesium borate whiskers, zirconium diboride and cellulose nanofibers to the pre-hydrolyzed silane coupling agent is 1:0.03; In step (1)②, the mass ratio of magnesium borate whiskers, zirconium diboride and cellulose nanofibers is 1: 0.7-0.9: 1.2-1.

3.

3. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: The first anhydrous ethanol solution and the second anhydrous ethanol solution in step (2) have the same composition, both being a mixture of anhydrous ethanol and deionized water in a volume ratio of 9:1; In step (2)①, the mass and volume ratio of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide to the first anhydrous ethanol solution is 1:20, in units of g / mL.

4. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: In step (2)①, the mass ratio of nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide is 1.2-1.4: 0.7-0.8: 0.55-0.

65.

5. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: In step (2) ②, the KH570 silane coupling agent accounts for 6-8% of the volume of the second anhydrous ethanol solution; The volume of the first anhydrous ethanol solution in step (2) ① is equal to the volume of the second anhydrous ethanol solution in step (2) ②.

6. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: In step (3), the outer layer raw material composition is as follows, calculated by weight: 85-87 parts of metallocene linear low-density polyethylene, 13-15 parts of low-density polyethylene, 2-3 parts of ethylene-ethyl acrylate copolymer, and 8-10 parts of a mixture of modified magnesium borate whiskers, zirconium diboride and cellulose nanofibers.

7. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: In step (4), the raw material composition of the intermediate layer is as follows, in parts by weight: 44-46 parts of metallocene linear low-density polyethylene, 31-33 parts of linear low-density polyethylene, 21-25 parts of low-density polyethylene, 3-5 parts of maleic anhydride grafted polyethylene, and 6.7-7.5 parts of a mixture of modified nano-molybdenum disulfide, nano-silicon dioxide and nano-titanium dioxide.

8. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: In step (5), the melt extrusion temperature of the inner layer raw material is 190-195°C; the melt extrusion temperature of the outer layer raw material is 190-200°C; the melt extrusion temperature of the middle layer raw material is 175-195°C; and the co-extrusion temperature is 210-215°C.

9. The method for preparing a high-strength disposable bioreactor bag according to claim 1, characterized in that: In step (5), the heat treatment temperature is 120-125° C. and the heat treatment time is 17-17.5 h.

Citation Information

Patent Citations

  • High-strength and corrosion-resistant modified polypropylene material

    CN109403014A

  • Preparation method of high-antibacterial PE (polyethylene) barrier film

    CN118165331A